Tourism Village Development Strategy through Community-Based Tourism and Women’s Empowerment for Sustainable Development in Bakau Serip. - Anggraini, Ratih; Arianto, Hepy Hefri; Putra, Edy Yulianto; Nainggolan, Ferdinand; Sudhartio, Lily; Purwianti, Lily; Setyawan, Agustinus; Aliandrina, Dessy; Chandra, Budi; Ivone, Ivone (Universitas Internasional Batam, 2024)
This study focuses on the development strategy of tourism villages through the implementation of Community Based Tourism (CBT) and women's empowerment as an effort to achieve Sustainable Development Goals (SDGs) in Kampung Tua Bakau Serip, Nongsa District. Tourism villages are crucial drivers of sustainable economic and environmental development in Indonesia, yet challenges remain in optimizing human resources and managing village potential. Through partnerships between Batam International University, local communities, and corporate social responsibility (CSR) programs, various capacity-building initiatives were implemented, particularly emphasizing women's participation in creative economy activities. The development roadmap envisions Kampung Tua Bakau Serip as a